Evaluation of School Children Crossing Facilities and Traffic Conflicts in The Vicinity of Schools in Selangor (International Journal of Built Environment and Sustainability, 2022)
Half of the world’s road traffic deaths involve vulnerable road users—pedestrians, motorcyclists, and cyclists. In Malaysia, there are several strategies introduced to improve the road safety level of school children. However, crashes involving school children are still worrisome. Recent trends of school children involved in crashes in school vicinity have become the nation’s concern. Therefore, this study aims to investigate the contributing factors of pedestrian-vehicle conflict involving school children in vicinity of the school. This study focused on the utilization of the facilities provided at school, exposure measures, and demographic characteristics of the schools. The facilities that are being considered in this study are; a zebra crossing, pedestrian bridge, drop-off, and pick-up zone, and the presence of a traffic warden. A total of 57 schools in Selangor were assessed for this study. The important variables were analyzed using the Negative Binomial Regression model to identify the significant attributes. Non-parametric analysis was used to compare the differences in characteristics of the schools. The findings of the study conclude that the road type and pedestrian volume are the underlying factors that would increase pedestrian-vehicle conflict in the school vicinity.
Keywords: Crossing, Conflict, School Children, School Vicinity, Negative Binomial